An evaluation of subcutaneous daratumumab for the treatment of multiple myeloma. Issue 8 (2nd August 2020) - Paul, Barry; Atrash, Shebli; Bhutani, Manisha; Voorhees, Peter; Hamadeh, Issam; Usmani, Saad Z.
ABSTRACT: Introduction: A subcutaneous formulation of daratumumab, a human immunoglobulin G1 kappa monoclonal antibody targeting CD38, recently achieved FDA approval for both newly diagnosed and relapsed refractory multiple myeloma amid promises to decrease infusion times and rates of infusion reactions in myeloma patients. Areas covered: In this article the biology behind subcutaneous administration of oncologic antibody therapies is reviewed and the subcutaneous formulation of daratumumab is covered in depth. The most recent results from the PAVO, COLUMBA, and PLEIADES clinical trials evaluating subcutaneous daratumumab as a single agent, and in combination, in both newly diagnosed, and relapsed and refractory myeloma patients are summarized. The efficacy, safety, and PK data from these trials are reviewed, and the potential of the subcutaneous formulation to improve quality of life in myeloma patients and decrease healthcare resource use is discussed. Expert opinion: Subcutaneous daratumumab is non-inferior to conventional intravenous daratumumab with lower risk of infusion-related reactions and decreased administration time. Based on these data, and the recent FDA and European Commission approvalsthe widespread use of the subcutaneous formulation for both conventional and investigational practice is supported.